إشكالية الحديث المتواتر من خلال كتاب الكتاني: دراسة تحليلية تاريخية - بريكي، محمد أحمد شعيلان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study is an attempt to explore the important aspect of Hadith mutawatir (successive narration): to highlight its essence, to explore its treasures; to distinguish it from what resembles to it, and to liberate it from stagnation. Scholars are divided into two the categories with regards to successive narration: those who strictly reject its existence, and liberals who accept everything to enter into it. The research explains the origin of the concept of Mutawatir, and its later development, which was not witnessed during the time of the companions and well-known imams in the Golden Era (of Islam). However, philosophers and theologians from among the Mu'tazila and others, who do not accept a Hadith unless it is Mutawatir there appeared among the (Muslim) ummah in the second century. Their aim was to demolish some essential pillars of religion that were established by Akhbar al-A'had among the generality of the Muslims. Thereafter, appeared some jurists (Usuliyyin) who had been influenced by the study of logic to become next to talk on the issue of Mutawitir after the Mu'tazila, but, with good intention. They reported it as tawatur al-tabaqa, similar to tawatur of Qura'n and showed that specialization (on tawatur) is not confined to Hadith scholars. This issue (of tawatur) then continued among Hadith scholars in the fifth century. The first who mentioned it from among the scholars of Hadith was Khatib al-Baghdadi, T. (463 AH). Consequently, it became part of Hadith sciences although many (scholars of Hadith) opposed the view of the Usuliyyin, and say that tawatur of Hadith is actually tawatur of chain (of narrators), not (like) the tawatur of the Quran. The researcher elaborates the different opinions in terms of the number that makes (Hadith) mutawatir, and provides evidences that indicate otherwise. Some scholars emphasized such greatly and put condition which led to the rejection of the existence of Hadith Mutawatir. On the other hand, others toleratehd in such manner that allowed many hadith ahad in hadith mutawatir. In conclusion, this research strikes a middle ground, that tawatur can be obtained with few (narrators) above that of Hadith mashhur, if is surrounded with reasonable evidence. This is the outcome of the research on the critical book “Nuzum al-Mutanāthir fi al-Hadith al-Mutawatir, li al-Kattāni. It comes after an analytical study and evaluation of Hadith (in the book), whether they have met the standard of tawatur or not? In case they do not meet up to standard, are they weak or authentic? The shdy also fownd answere to the following the number of Hadith studied, and how many Hadith meet the standard of tawatur? What are their wordings and meanings? What is the number of Hadiths which do not reach the standard of tawatur? What are the authentic and weak hadith (among them)?